Fostering communication strategies in children with hearing impairment - Hall, Winnifred M.
The purpose of this report is to review some concepts derived from the literature, which can be used as a basis for developing a remediation programme and to present a programme based on these concepts. The paper is therefore in two sections: 1) a discussion of the related literature, and 2) the presentation of a programme designed for participants in the Certificate in Education of the Hearing Impaired Course conducted at The University of the West Indies (UWI)
Keywords: Hearing impaired students